Studi Kualitatif Mengenai Pengetahuan Perpajakan dan Kepatuhan Wajib Pajak Pengusaha E-Commerce - Jihan Alfadila; Hotmavica Natalia; Iswandi; Rimi Gusliana Mais; Uun Sunarsih (Journal of Economics and Business Aseanomics, 2024)
This research aims to determine the perceptions of e-commerce entrepreneurs regarding tax obligations. This research uses qualitative methods with an interpretive paradigm in order to explain social world phenomena from the perspective of e-commerce entrepreneurs. The research subjects are e-commerce entrepreneurs with gross turnover of between IDR 500 million and IDR 4.8 billion per year. The results of this research indicate that business actors are aware of taxes but do not have sufficient understanding to fulfill their tax obligations, so they tend to prefer to hand it over to employees who have a tax background. Three participants met all the criteria for compliant taxpayers. The other two participants did not carry out most of their tax obligations, which will result in tax arrears in the future.